Pengaruh Pemberian Jus Bayam terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil dengan Anemia Ringan - Marchatus Soleha; Tiara Fatrin; Karmila Karmila (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Anemia is a condition of mothers with hemoglobin (Hb) levels in the blood less than 12 g%, so that it can increase the risk of premature birth, maternal and child mortality, and infectious diseases. To overcome anemia in pregnancy, one of them is by drinking spinach juice as an alternative way to increase hemoglobin levels in pregnant women. This study aimed to determine the effect of drinking spinach juice on increasing hemoglobin levels in pregnant women with mild anemia. This study used the literature study method, so an analysis of the search results of journals (e-journals) and articles was carried out with a review of existing theories (e-books). This study revealed that the duration of drinking spinach juice which was effective in increasing hemoglobin levels in pregnant women with mild anemia was for 10 days with the amount of spinach was 100 grams of spinach and 150 ml of boiled water with a frequency of 1x1 day and there was no different effectiveness between the method of giving spinach juice and consuming spinach as vegetable. Health workers, especially midwives, could provide counseling and education to pregnant women related to the effect of drinking spinach juice on increasing hemoglobin levels as an alternative way to increase hemoglobin levels.